Complex Borrowing words in Russian and English Slang: A Structural Analysis - Davlyatova Elvira Muradovna, Bazarova Karina (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
This study investigates the phenomenon of complex borrowing in the realm of slang within the Russian and English languages. Slang, as a dynamic component of language, serves as a window into cultural and social dynamics, reflecting the evolving identities and communication patterns of its speakers. While borrowing between languages is a well-documented phenomenon, the process of complex borrowing in slang involves the adoption and adaptation of foreign linguistic elements into the native lexicon, often resulting in innovative structural formations. Drawing upon a variety of linguistic sources, including dictionaries, corpora, and online forums, this research employs a comparative analysis to explore the structural aspects of complex borrowing in Russian and English slang. The study examines lexical innovations, word formation processes, and syntactic patterns that emerge as a result of complex borrowing, shedding light on the mechanisms through which foreign influences shape the linguistic landscape of slang. The findings reveal intriguing parallels and divergences between Russian and English slang, highlighting the nuanced ways in which complex borrowing manifests in each language. From loanwords and loan-blends to hybrid grammatical constructions, the structural analysis uncovers the dynamic interplay between linguistic creativity and cultural exchange within the slang register. Furthermore, this study considers the sociocultural implications of complex borrowing, examining how linguistic borrowing reflects broader trends in globalization, cultural exchange, and identity construction. By delving into the intricacies of complex borrowing in Russian and English slang, this research contributes to a deeper understanding of language variation and cultural dynamics in the contemporary world.